Peran Kualitas Pelayanan dalam Meningkatkan Kepuasan Konsumen: Studi Kasus pada McDonald's - Kezia Rostiana; Galih Tri Bawono; Daniel Vieri (Ebisnis Manajemen, 2024)
This study discusses the role of service quality in increasing customer satisfaction with a case study at McDonald's. Service quality is an important factor in the fast food restaurant industry, especially to create positive experiences, loyalty, and customer satisfaction. Through a qualitative approach based on literature review, this study analyzes service dimensions, such as speed, responsibility, and staff attitude that affect customer experience. The results of this study indicate that speed of service, employee friendliness, and product consistency are the main factors in shaping customer satisfaction at McDonald's. Therefore, the use of technology such as self-ordering machines and application-based services contribute significantly to increasing efficiency and customer satisfaction. McDonald's also strives to maintain standards of efficiency and customer comfort facilities. This study emphasizes the importance of consistently improving service quality in creating loyalty and strengthening brand image amidst competitive competition.